Hasil Penelitian PENERAPAN LEMBAR REFLEKSI BACAAN UNTUK MENUMBUHKAN KARAKTER GEMAR MEMBACA PADA SISWA SEKOLAH DASAR - Khamim Wahyudi; Wildan Nurul Fajar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the implementation of the Reading Reflection Sheet (RRS) in fostering the character of reading enjoyment among elementary school students, analyze changes in students’ intrinsic reading motivation and reflection quality, and identify supporting and inhibiting factors in its implementation. The study employed a qualitative approach with a case study design conducted in a fifth-grade class at SDN Pegadingan 04. The participants consisted of 20 students, a classroom teacher, and the school principal. Data were collected through observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings revealed that the implementation of the Reading Reflection Sheet was carried out through three stages: preparation, trial, and full implementation integrated into the school’s morning literacy program. The use of the RRS encouraged students not only to read but also to understand, interpret, and reflect on the content of their reading materials. The program contributed to the enhancement of intrinsic reading motivation, as indicated by increased interest in reading, greater initiative in selecting books based on personal preferences, voluntary reading habits, and more active participation in discussions about reading materials. Students’ reflection quality also improved, as demonstrated by their ability to identify moral messages, relate reading content to personal experiences, and formulate actions based on values obtained from the texts. The successful implementation of the program was supported by the school literacy culture, support from the principal, teachers, parents, and the availability of reading materials. The main challenges included differences in students’ reflection abilities, limited implementation time, and the low self-confidence of some students. The findings indicate that the Reading Reflection Sheet can enrich school literacy programs and support the development of students’ reading enjoyment character.